2015
DOI: 10.1104/pp.114.247403
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Origin and Evolution of the Plant Hormone Signaling Machinery

Abstract: Plant hormones modulate plant growth, development, and defense. However, many aspects of the origin and evolution of plant hormone signaling pathways remain obscure. Here, we use a comparative genomic and phylogenetic approach to investigate the origin and evolution of nine major plant hormone (abscisic acid, auxin, brassinosteroid, cytokinin, ethylene, gibberellin, jasmonate, salicylic acid, and strigolactone) signaling pathways. Our multispecies genome-wide analysis reveals that: (1) auxin, cytokinin, and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
190
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(223 citation statements)
references
References 89 publications
(142 reference statements)
3
190
1
1
Order By: Relevance
“…The PP pathway is also a source for SA biosynthesis [122]. Moreover, potential homologs for the SA receptor Nonexpressor of PR genes 1 (NPR1) [123], were reported for all land plants [113] and the putative NPR1 homolog of P. patens can partially complement defense signaling-associated phenotypes of the Arabidopsis npr1 mutant [124]. As for ET, recent studies showed that streptophyte algae produce, sense and respond to ET [112,115], but these studies did not dissect the role of ET as a hormone involved in defense.…”
Section: Evolution Of Phytohormone Defense Networkmentioning
confidence: 99%
“…The PP pathway is also a source for SA biosynthesis [122]. Moreover, potential homologs for the SA receptor Nonexpressor of PR genes 1 (NPR1) [123], were reported for all land plants [113] and the putative NPR1 homolog of P. patens can partially complement defense signaling-associated phenotypes of the Arabidopsis npr1 mutant [124]. As for ET, recent studies showed that streptophyte algae produce, sense and respond to ET [112,115], but these studies did not dissect the role of ET as a hormone involved in defense.…”
Section: Evolution Of Phytohormone Defense Networkmentioning
confidence: 99%
“…[7][8][9][10] Plant hormones are found not only in higher plants, but also in algae, and in plant-associated bacteria and fungi. [11][12][13] However, in this case, plant hormones are not the essential small molecular necessary to the growth and reproduction of the microorganisms. Thus they are regarded as secondary metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, SLs may regulate shoot branching patterns in parasites just as in other eudicots, and Liu et al [33] suggest that SLs are important in regulating branching in Striga. SL hormones are evolutionarily ancient and understanding of their role in coordinating plant development is rapidly expanding [14] [32]. The current work contributes to this body of knowledge by demonstrating that parasitic plant synthesis of SLs and use as germination triggers is likely more sophisticated than initially expected.…”
Section: Discussionmentioning
confidence: 64%
“…The origin of AM fungi symbiosis and shoot branching is ancient [11], and there is evidence that all angiosperms and even lower plants such as mosses and liverworts produce SLs [12]- [14]. However, the requirement of Orobanche, Phelipanche and Striga for exogenous SLs raises questions about how these species have evolved to respond to exogenous SLs and whether this trait could involve a loss in SL biosynthetic ability [15].…”
Section: Introductionmentioning
confidence: 99%